IMPROVING BUSINESS MANAGEMENT EFFICIENCY THROUGH STRATEGIC PLANNING, DIGITAL TRANSFORMATION, AND PERFORMANCE OPTIMIZATION IN UZBEKISTAN - Maftuna Muslimova Botirjon qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
This study explores the improvement of business management efficiency in Uzbekistan through the integration of strategic planning, digital transformation, and performance optimization approaches. In the context of a rapidly developing economy, effective management systems are essential for increasing competitiveness, enhancing productivity, and ensuring sustainable business growth.The research analyzes how strategic planning contributes to long-term organizational stability, while digital transformation improves operational speed, data-driven decision-making, and service quality. Additionally, performance optimization is examined as a key factor in reducing inefficiencies and increasing overall business output.The study highlights that businesses in Uzbekistan are gradually adopting modern management tools such as enterprise resource planning (ERP) systems, digital analytics platforms, and automated workflow solutions. However, challenges such as limited digital infrastructure, skill gaps, and adaptation barriers still exist.